2011
DOI: 10.1007/bf03256923
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of a Fixed-Dose Combination of Atorvastatin and Metformin Extended Release versus Concurrent Administration of Individual Formulations

Abstract: Atorvastatin/metformin ER 10 mg/500 mg FDC has similar bioavailability to the co-administration of separate atorvastatin 10 mg and metformin 500 mg tablets. The FDC tablets show similar safety and tolerability profiles to their individual components. Therefore, atorvastatin/metformin ER 10 mg/500 mg FDC tablets can be used safely in clinical settings to decrease the pill burden and increase patient compliance with therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…There are several published BE studies of metformin FDC formulations that have reported bioequivalence relative to country‐sourced metformin formulations (Table ), except for C max , which was slightly outside the bioequivalence range of 80%–125% in 1 of the studies . Similar to IR formulations, interestingly, modified‐release metformin formulations have also shown bioequivalence relative to country‐sourced formulations . Although modified‐release formulations are not discussed in this article, it is intriguing that bioequivalence is also reported relative to country‐sourced metformin, which emphasizes consistent metformin PK despite different country‐source, formulation and subjects.…”
Section: Discussionmentioning
confidence: 96%
“…There are several published BE studies of metformin FDC formulations that have reported bioequivalence relative to country‐sourced metformin formulations (Table ), except for C max , which was slightly outside the bioequivalence range of 80%–125% in 1 of the studies . Similar to IR formulations, interestingly, modified‐release metformin formulations have also shown bioequivalence relative to country‐sourced formulations . Although modified‐release formulations are not discussed in this article, it is intriguing that bioequivalence is also reported relative to country‐sourced metformin, which emphasizes consistent metformin PK despite different country‐source, formulation and subjects.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, several other antidiabetic or related therapeutic agents have been developed into FDCs, including saxagliptin/metformin XR and atorvastatin/ metformin XR. 16,17 Establishing a treatment strategy that incorporates FDCs may simplify diabetes treatment regimens and support the management of concurrent conditions also requiring drug treatment by reducing the pill burden on patients.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive pharmacy care program with the use of one-dose packages led to an increase in good adherence of medications 9. Fixed-dose combinations have been developed,5,1014 such as antihyperglycemic agent or calcium-channel antagonist and β-hydroxy-β-methylglutaryl-CoA (HMG-CoA) reductase inhibitor, to limit the effect of lifestyle-related diseases, such as diabetes, hyperlipidemia, and hypertension. Indeed, fixed-dose combinations with five different medications have been developed in India 14.…”
Section: Discussionmentioning
confidence: 99%
“…Various measures aimed at improving patient medication adherence are needed; in particular follow-up by a telephone-based nursing strategy8 and medications dispensed in time-specific packs or one-dose packages at pharmacies 9. In terms of pharmaceutical improvement, a fixed-dose combination with two or more medications has been developed as part of a risk evaluation and mitigation strategy 5,1014. However, good adherence by the patient cannot be assured if he/she is not convinced about the necessity of the prescribed medication.…”
Section: Introductionmentioning
confidence: 99%